Experimental evidence for the effects of the Demand-Control model on the cognitive arousal: An EEG based study - Subhani, A.R. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Demand-Control (DC) model has been extensively researched to find the imbalance of demand and control that cause work-related stress. Past research has been exclusively dedicated to evaluate the impact of this model on employees' well-being and job environment. However, the impact of high demands (strain hypothesis) and the influence of control (buffer hypothesis) on cognitive arousal have yet to be identified. We aimed to fill this void by measuring the influence of the DC model on the cognitive arousal. Electroencephalogram (EEG) was recorded to extract the cognitive arousal in an experiment that implemented the DC model. The experiment comprised four conditions having combination of varying demand and control. The strain and the buffer hypothesis were separately validated by the cognitive arousal in association with the task performance and subjective feedbacks. Results showed the maximum arousal and the worst performance occurred in high demand and low control condition. Also high control proved to significantly lower arousal and improved performance than in low control condition with high demand. Â© 2015 IEEE.